2020
DOI: 10.1007/s00423-020-01938-4
|View full text |Cite
|
Sign up to set email alerts
|

Preventing chylous ascites after right hemicolectomy with D3 extended mesenterectomy

Abstract: Background We aim to find the incidence of chylous ascites in patients undergoing D3 extended mesenterectomy and evaluate if a routine fat-reduced diet (FRD) has a prophylactic effect. Methods Data from 138 patients included in a D3 extended mesenterectomy trial were collected prospectively. Surgical drains and biochemical testing of drain fluid were used to find the incidence of chylous ascites among the first 39 patients, and a prophylactic fat-reduced diet was then implemented in the next 99 patients as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…As the principle of D3 Lymphadenectomy is to remove more LNs in the mesenteric root, the number of LNs retrieved was quite large, but it was still less than in the study by Liang et al [ 17 ] (25.9 ± 8.7 vs 34.4 ± 8.4, P < 0.05). Due to the larger area of lymph node removal in D3 extended mesenterectomy, CA was more likely to occur, which was confirmed in Agustsdottir EES’s study that the incidence of CA after D3 extended mesenterectomy was 41.0%[ 18 ], which was higher than our data (41.0% vs 9.7%). Somatostatin, or its synthetic analog octreotide, which can reduce the absorption of triglycerides and inhibits visceral circulation and gastrointestinal motility, thereby reducing the concentration of triglycerides in the thoracic duct and reducing the lymphatic flow of the main lymphatic vessels[ 19 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As the principle of D3 Lymphadenectomy is to remove more LNs in the mesenteric root, the number of LNs retrieved was quite large, but it was still less than in the study by Liang et al [ 17 ] (25.9 ± 8.7 vs 34.4 ± 8.4, P < 0.05). Due to the larger area of lymph node removal in D3 extended mesenterectomy, CA was more likely to occur, which was confirmed in Agustsdottir EES’s study that the incidence of CA after D3 extended mesenterectomy was 41.0%[ 18 ], which was higher than our data (41.0% vs 9.7%). Somatostatin, or its synthetic analog octreotide, which can reduce the absorption of triglycerides and inhibits visceral circulation and gastrointestinal motility, thereby reducing the concentration of triglycerides in the thoracic duct and reducing the lymphatic flow of the main lymphatic vessels[ 19 ].…”
Section: Discussionsupporting
confidence: 84%
“…This may be part of the reason why our incidence of CA was lower than that in other studies. The study by Agustsdottir et al [ 18 ] considered that a routine fat-reduced diet (FRD) had a prophylactic effect and prevented the lymphatic vessels from collapsing, thereby reducing the occurrence of CA. According to our study, somatostatin played a protective role, indicating that somatostatin administration can reduce the occurrence of CA, but there is currently no relevant research to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From there, the intestinal lymph or chyle (which also contains chylomicrons) is transported via the intestinal trunk(s) to the cisterna chyli and then through the thoracic duct into the left venous angle. While the peripheral [ 7 , 8 , 9 ] and the central [ 10 , 11 , 12 ] mesenteric lymphatics have been thoroughly studied, the link between them, i.e., immediate affluents of the intestinal trunk, is still scarce in the literature, even though they are of paramount clinical significance in gastric, colorectal, small bowel and pancreatic surgery, e.g., in cases of chylous ascites [ 13 ]. Further, it has been reported that lymph vessels draining the pancreas can open directly into the thoracic duct or via para-aortic lymph nodes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Central vascular ligation and D3 lymphadenectomy during CME for right hemicolectomy enables more radical removal of the metastatic lymph nodes around the SMA and theoretically would improve the oncological outcome. However, it may cause iatrogenic injury to abundant lymphatic tributaries near the cisterna chyli and thus increase the occurrence of postoperative chylous ascites [9]. Currently, few studies are focused on chylous ascites following right hemicolectomy with CME [10].…”
Section: Introductionmentioning
confidence: 99%